متشدد رویے اورعدم برداشت کابین الاقوامی رحجان: سیرت طیبہ کے تناظر میں ایک مطالعہ : International Tendency of Violent Attitudes and Coercion: A Study in the Light of Prophetic Teachings - Dr. Muhammad Sarwar; Azhar Farid; Hafiz Muhammad Tanzeem (Al-Qamar, 2020)
It is the established fact that humanity is facing problems such as violent attitudes, coercion and terrorism. Extremist attitudes towards humanity have created a precarious situation. This situation can lead to a major conflict. This conflict may forget all the catastrophic events of the past, including World Wars I and II, and humanity may face an unimaginable loss. Violent tendencies in our individual and collective attitudes are increasing day by day. Policies and actions are also a reflection of this situation at national and international level. The roots of extremism, whether in the form of aversion to religion or in the form of religiosity, are not only spreading racial, linguistic and religious rapidly but also becoming stronger and stronger. The sectarian differences have hurt humanity. The hot market of rumors and disrespect for the law and its supremacy seem to be lacking. Extremism and sentimentalism are creating problems for humanity. These problems cannot be solved in scientific laboratories but through moral teachings. Relationships of brotherhood, tolerance are being undermined. International terrorism, sectarianism are ugly examples of violent attitudes.